UNUSUAL PRESENTATION OF UNUSUAL HEPATITIS - Sunil Kumar Dodani; Bader Faiyaz Zuberi; Rashid Qadeer; Abdul Rauf Memon; Inayat Baloch; Salahuddin Afsar (Journal of the Dow University of Health Sciences, 2007)
Chronic hepatitis is common in Pakistan and most frequent causes are various viral hepatitis, while occasionally other causes like a alcohol, Wilson’s disease and, hepatitis (AIH) is an uncommon disease in Pakistan. It is characterized histologically by interface hepatitis, and serologically by the presence of non-organ and liver specific autoantibodies and increased levels of immunoglobulin G. Its onset is often ill-defined, frequently mimicking acute hepatitis. An interesting case of AIH with unusual presentation is being presented in this report.